Youth sexual offending in Hong Kong: examining the role of self-control, risky sexual behaviors, and paraphilic interests - Chan, Heng Choon (Oliver) (Frontiers in Psychiatry, 2023)
Little is known about the prevalence and nature of youth sexual offending in Hong Kong. Testing self-control theory and sexual health risk factors (i.e., risky sexual behaviors [general and two subtypes] and paraphilic interests [general and 14 subtypes]), the prevalence of self-reported sexual offending behaviors (i.e., threat of sexual assault, penetrative sexual assault, and nonpenetrative sexual offense) was examined in a community-based sample of 863 young people (aged 17 to 20) in Hong Kong. The findings indicated that men reported significantly higher levels of threat of sexual assault and of general and 12 subtypes of paraphilic interests than women; and women reported a significantly higher level of a specific paraphilic interest subtype (i.e., transvestic fetishism) than men. Logistic regressions found that, in general, a low level of self-control and high levels of risky sexual behaviors and paraphilic interests were important factors in the participants’ likelihood of issuing threats of sexual assault and engaging in penetrative and nonpenetrative sexual assault. The findings of this study have important practical implications for reducing the tendency of young people to engage in sexual offending behavior.